Stress-Free Collection Of Continuous Rodent Behaviors And Ultrasounds Vocalization (Usv) Data For Autism Study And The Need For Multi-Dimensional And Multi-Functional Measurement In Preclinical Study For Autism Research - Bachdasarian, Levon
Աուտիզմը որին բնորոշ են աուտիկ սպեկտրի խանգարումները` ԱՍԽ, հոգեկան հիվանդություն է, որն առաջ է գալիս ժառանգական ֆոնի և միջավայրի բարդ փոխազդեցության հետևանքով: Ախտանշաններն են սոցիալական հաղորդակցման, ուշադրության և տեղեկատվության մշակման անբավարարությունը, կենտրոնացման դեֆիցիտը, շփման խանգարումները, գերակտիվությունը, ցավի նկատմամբ ընկալունակության նվազումը, վարքի կրկնվող տարբեր ձևերը: Ներկայումս աուտիզմը կամ ԱՍԽ-ն, ախտորոշում են վարքային ֆենոտիպացման, այլ ոչ թե նեյրոկենսաբանական թերությունների միջոցով: Заболевание аутизмом имеет расстройство аутистического спектра (РАС) - это психическое заболевание, которое возникает из-за сложного взаимодействия между генетическим фоном и окружающей средой. Симптомами являются дефицит социального взаимодействия, нарушения коммуникации, обработки информации и внимания, дефицит концентрации, гиперактивность, уменьшения чувствительности к боли и несколько повторяющихся форм разных поведении. В настоящее время аутизм или РАС диагностируют на основе поведенческих фенотипированием, а не нейробиологических дефектов. Autism disease has Autism Spectrum Disorder (ASD) is a psychiatric disease that is caused due to the complex interplay between genetic and environmental background. The symptoms are social interaction deficits, communication impairments, information processing and attention, concentration deficits, hyperactivity, less sensitive to pain and several repetitive behaviors. Autism disease or ASD is currently diagnosed based on the behavioral phenotypic traits, rather than neurobiological defects.
Keywords: Psychology